‘Meat and eggs’ dietary pattern in overweight and obese adolescents and its relationship with cardiometabolic markers (Revista Contexto & Saúde, 2025)
To associate dietary patterns with cardiometabolic markers in overweight and obese adolescents. A cross-sectional study was conducted with 227 adolescents aged 10 to 19 years, who were attending six public healthcare services in a city in Southern Brazil. A semi-quantitative food frequency questionnaire was administered. Dietary patterns were identified using principal component analysis followed by orthogonal Varimax rotation. Independent associations between dietary patterns and marker values (glucose, fasting insulin, Homeostatic Model Assessment index, total cholesterol, triacylglycerols, Low-Density Lipoprotein, High-Density Lipoprotein, cholesterol not transported by HDL, C-reactive protein, and blood pressure) were tested using quantile regression. The scores of dietary patterns were categorized into tertiles and associated with the outcomes of altered cholesterol transported by HDL or triacylglycerols levels due to their significant associations. A significance level of p